Serving in the Indian diaspora: The transnational domestic servant in contemporary women's fiction. Issue 1 (2nd January 2019) - Mirza, Maryam
Abstract: While substantial attention has been paid to the depiction of racial and cultural othering experienced by middle-class female Indian immigrants in the Global North, this article grapples with a rare figure in the fiction of the Indian diaspora: a female immigrant employed as a live-in domestic worker. By focusing on the novel Jasmine (1989) by Bharati Mukherjee and two short stories, "A Pocket Full of Stories" (2009) by Sujatha Fernandes and "Almost Valentine's Day" (2014) by Mridula Koshy, the article examines how these divergent representations of domestic servitude complicate prevailing interpretations of the Indian diasporic experience, particularly by requiring an engagement with the complex intersection of class, race and gendered identities. Moreover, as this article demonstrates, with their contrasting ideological underpinnings, the three works compel readers to revisit the myth and reality of upward social mobility, and to reconceptualize the meaning of integration and exclusion in a transnational context.